Terapia fotodynamiczna z użyciem verteporfiny w leczeniu neowaskularyzacji podsiatkówkowej w wieloogniskowym zapaleniu błony naczyniowej - Gębka, Andrzej; Raczyńska, Krystyna; Ciechanowski, Cezary; Krajka-Lauer, Jarosława (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Apart from AMD and pathologic myopia the posterior uveitis is the most common pathology being the cause of secondary choroidal neovascularisation (CNV). For many years the method of choice in treating those pathologies was the theramal laser photocoagulation with obvious limitations in the cases of subfoveal CNV. The implementation of PDT modality to every day's clinical practice expanded the range of CNV treatment methods. The following case report shows the results of treating the CNV secondary to multifocal choroiditis with PDT. During the 6 months of follow-up period we consider PDT as an effective, safe modality in treating the CNV secondary to inflammation. In the result of single PDT therapy the VA improvement of 4 ETDRS lines and it's stabilization on the level of 20/25 with the decrease of metamorphopsia was gained.